Preliminary Report : The Treatment of Withdrawal Symptoms of Opium Addicts with Vitamin " E " in Ten Cases - H. Davidian (Acta Medica Iranica, 1957)
The treatment of addiction to opiates, apart from psychological and social problems, has presented up to now a therapeutic prohlem. Various methods are used and each has its disadvantages. Residual symptoms of abstinence from opiates are present in all methods and there is a prolonged period of convalescence which seems to be one of the causes of relapses to addiction. Vitamin E however- has given remarkable results in aiding recovery from the withdrawal symptoms. With vitamin E the period of treatment is shortened, abstinence symptoms are bearable and the convalescent period is eliminated. Patients treated with vitamin E solely are in good health and spirits and appear contented. This treatment also seems to reduce 1he number of relapses. The administration of vitamin E after a complete withdrawal from opium probably compensates Some of the opium's effects on the nervous system, and remedies the hypoxia of the tissues, thus restoring the patient to a normal physiological state.